Uniting mountain & plain : cities, law, and environmental change along the front range - Brosnan, Kathleen A., 1960- (University of New Mexico Press, 2002)
"By linking widely separated ecosystems in the urban-based economy of the Front Range, Brosnan notes, entrepreneurs created irrevocable environmental change and restructured the relations of the region's inhabitants with the land and with each other. Hispanic and Native American people who had lived in Colorado since long before the gold rush found themselves marginalized or displaced, foreshadowing the subsequent surrender of regional industries to the Goulds, Guggenheims and Rockefellers by the early twentieth century."--Jacket